Comparative study on the efficacy of intra-articular steroid injection through glenohumeral versus subacromial approach in the treatment of adhesive capsulitis - Ghorai, Debayan; Mondal, Sumantro; Basak, Amalesh; Kamal, Firdaus (International Journal of Research in Medical Sciences, 2020)
Background: Objective of the study was to compare the efficacy between gleno-humeral and sub-acromial approach of intra-articular steroid injection in the management of adhesive capsulitis. Methods: This study was a randomized parallel group, open label, interventional study conducted during the period of May 2018 to October 2019. Patients with stage1 or stage2 adhesive capsulitis of shoulder (n=56) were selected and after computer generated randomization they were allocated into two groups (gleno-humeral and sub-acromial) consisting of 28 patients in each group. Gleno-humeral and sub-acromial group received intra-articular injection of 40 mg (1ml) depot methylprednisolone acetate with 2 ml of 2% lignocaine through gleno-humeral and sub-acromial approach respectively along with physical therapy. Primary outcome measure was improvement of range of motion of intervened shoulder joint from the baseline to 3rd and 6th weeks post injection. Secondary outcome measures were VAS, physician and patient’s global assessment of pain and functional status. Results: At baseline and 3rd post-injection none of the outcome parameters showed statistically significant difference between those two groups. At 6th post-injection sub-acromial group showed statistically significant improvement in active flexion (p value=0.040), passive flexion (p value=0.024), passive abduction (p value=0.044) and physician’s global assessment score (p value=0.017). Conclusions: Sub-acromial approach of injection is better than gleno-humeral approach in terms of improvement in flexion, passive abduction and physician’s global assessment score at 6th post-injection in patients with stage1 or stage2 adhesive capsulitis.